Naglalayag (Silent passage) (Regal Films, 2004)
Dorinda is a widow and menopousal. Being incorruptible RTO judge, she finds herself too alone and frightened after the pronouncement of her decision in a recently concluded trial. On that stormy night, she is in a hurry to leave her office thus forgets all the keys including her car key. She is left without a choice but to take a cab. She meets Noah, the young taxi driver, half her age.